Development Strategies Village Owned Enterprises Case Study on BUMDes Mutiara Arta - Yuda Prasetya; Sucihatiningsih Dian Wisika Prajanti (International Business and Accounting Research Journal, 2023)
The village is a legal community unit that has territorial boundaries that are authorized to regulate and manage the interests of the local community, the village is also the lowest regional unit in the Indonesian state administration. Village-Owned Enterprises (BUMDes) as an institution owned by the village and are village economic institutions are expected to help rural communities to improve their economy. This study aims to determine the policy priorities that can be taken as a strategy for developing BUMDes, where BUMDes Mutiara Arta is the object of this study. This study uses Analytical Hierarchy Process (AHP) analysis to determine the strategy for developing BUMDes in the study in Batur Village, Getasan District, Semarang. Several limitations in this study such as research object which only includes 1 BUMDes, there were many other criteria factors that influenced the development of BUMDes and there were also limitations to research using a questionnaire, namely that sometimes the answers given by the sample did not show the actual situation Researchers also have not involved the community in the interview process. The results showed that the marketing factor was prioritized at (0.102). An alternative strategy for the second priority of developing BUMDes Mutiara Arta Batur Village, Getasan District, Semarang Regency is training of workers in increasing business innovation (0.083). An alternative strategy for the third priority of developing BUMDes Mutiara Arta Batur Village, Getasan District, Semarang Regency is the absorption of local workers (0.74). Therefore, the regional government, sub-district government and village government must be able to support, encourage and facilitate the development of BUMDes in Batur Village, Getasan District